Antiplasmodial potential of South African medicinal plants and phytochemical investigation of Aloe marlothii, Turraea obtusifolia and Artemisia afra for identification of their active compounds - Maharaj, Vinesh J. (University of Pretoria, 2023)
Thesis (PhD (Chemistry))--University of Pretoria, 2023.